PENDUGAAN CADANGAN KARBON TUMBUHAN BAWAH PADA TEGAKAN MINDI (Melia azedarach) DAN MAHONI (Swietenia macrophylla) - Immanuel Sihaloho; Muhdi Muhdi; Siti Latifah (Peronema Forestry Science Journal, 2016)
Measurement of carbon stock is very important to know how much carbon that can be absorbed by plants. Object of this research was the understorey on stands Mindi (Melia azedarach) and Mahoni (Swietenia macrophylla). The method of measurement used is the destructive sampling method that is the way to harvest the entire understorey which is at 1m x 1m sample plots.  The results of this study indicate that the type of stands under the influence of the composition of the existing understorey under the stand so that the carbon content in the understorey was different. The average of carbon understorey on the second stands is 1.08 tons/ ha. Keywords: understorey, Mindi (Melia azedarach) Mahoni (Swietenia macrophylla), carbon stock.